2013
DOI: 10.1007/s12041-013-0252-0
|View full text |Cite
|
Sign up to set email alerts
|

Last mated male sperm precedence in doubly mated females is not ubiquitous: evidence from sperm competition in laboratory populations of Drosophila nasuta nasuta and Drosophila nasuta albomicans

Abstract: Shruthi B. and Ramesh S. R. 2013 Last mated male sperm precedence in doubly mated females is not ubiquitous: evidence from sperm competition in laboratory populations of Drosophila nasuta nasuta and Drosophila nasuta albomicans J. Genet. 92, [309][310][311][312]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Interestingly, it has been observed that the last male sperm precedence in doubly mated females is not ubiquitous. In the nasuta species subgroup, two species Drosophila nasuta nasuta (P2 is 0.34) and Drosophila nasuta albomicans (P2 is 0.29) show first male sperm precedence which has been explained by suggesting that selection has not favored remating (Shruthi and Ramesh, 2013). Therefore, we conclude that the three species of the bipectinata complex i.e., D. bipectinata, D. parabipectinata and D. malerkotliana show variations in the pattern of sperm displacement although the intensity of sperm competition is highest in D. bipectinata.…”
Section: Speciesmentioning
confidence: 99%
“…Interestingly, it has been observed that the last male sperm precedence in doubly mated females is not ubiquitous. In the nasuta species subgroup, two species Drosophila nasuta nasuta (P2 is 0.34) and Drosophila nasuta albomicans (P2 is 0.29) show first male sperm precedence which has been explained by suggesting that selection has not favored remating (Shruthi and Ramesh, 2013). Therefore, we conclude that the three species of the bipectinata complex i.e., D. bipectinata, D. parabipectinata and D. malerkotliana show variations in the pattern of sperm displacement although the intensity of sperm competition is highest in D. bipectinata.…”
Section: Speciesmentioning
confidence: 99%